2022
DOI: 10.3389/fpsyt.2021.798554
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-Related Mortality Risk in People With Severe Mental Illness: A Systematic and Critical Review

Abstract: Background: Increasing clinical evidence suggests that people with severe mental illness (SMI), including schizophrenia spectrum disorders, bipolar disorder (BD), and major depressive disorder (MDD), are at higher risk of dying from COVID-19. Several systematic reviews examining the association between psychiatric disorders and COVID-19-related mortality have recently been published. Although these reviews have been conducted thoroughly, certain methodological limitations may hinder the accuracy of their resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 154 publications
0
45
0
6
Order By: Relevance
“…These findings are concerning given the fact that even before the pandemic, financial hardship, unemployment, and discrimination based on race/ethnicity had been identified in studies of Latino mental health to have a deleterious impact including development of psychiatric disorders such as depression [21][22][23]. As noted earlier in this analysis, research has shown that people with psychiatric disorders had poor COVID outcomes in comparison to those not struggling with mental health, which raises concerns that the combination of economic adversity and poor mental health could be contributing to Latino infection and mortality [4][5][6][7]9]. Our findings echo those of a previous survey that showed an overall socio-economic disadvantage for US Latinos during the COVID-19 pandemic including problems paying bills, reliance on food banks, struggles to afford health care, and lost health insurance [20].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…These findings are concerning given the fact that even before the pandemic, financial hardship, unemployment, and discrimination based on race/ethnicity had been identified in studies of Latino mental health to have a deleterious impact including development of psychiatric disorders such as depression [21][22][23]. As noted earlier in this analysis, research has shown that people with psychiatric disorders had poor COVID outcomes in comparison to those not struggling with mental health, which raises concerns that the combination of economic adversity and poor mental health could be contributing to Latino infection and mortality [4][5][6][7]9]. Our findings echo those of a previous survey that showed an overall socio-economic disadvantage for US Latinos during the COVID-19 pandemic including problems paying bills, reliance on food banks, struggles to afford health care, and lost health insurance [20].…”
Section: Discussionmentioning
confidence: 76%
“…Although there exists an emergent scholarship on Latino COVID-19 health outcomes and studies exploring the intersection of the virus and mental health, research probing the question of how the pandemic has affected Latino mental health remains sparse [1][2][3]. This issue is a critical avenue for inquiry, given that recent studies suggest that US adults as a whole who suffer mental health disorders are at escalated risk for COVID-19 infection, complications, and mortality [4][5][6][7][8][9]. An analysis of electronic health records from 61 million adult patients assessing the impact of a diagnosis within the past year of bipolar disorder, depression, attention-deficit/ hyperactivity disorder (ADHD), and schizophrenia found that a recent psychiatric disorder diagnosis significantly increased risk for COVID-19 infection [6].…”
Section: Introductionmentioning
confidence: 99%
“…The authors reported an association between pre-existing mood disorders and risk of hospitalization (OR = 1.31) and COVID-19–related death (OR = 1.51) but not increased susceptibility to COVID-19 (OR = 1.27) [ 142 ]. A recent systematic review painted an even more concerning picture, estimating a 2–4-fold increased risk of mortality in patients with schizophrenia and 1.5–2-fold greater mortality risk in individuals with MDD [ 143 ].…”
Section: Depression and Other Psychiatric Disorders As Risk Factors F...mentioning
confidence: 99%
“…Fourth, biological aging has been hypothesized to be accelerated in multiple psychiatric disorders [ 110 , 158 , 159 ] and older age is a risk factor for adverse outcomes after SARS-CoV-2 infection [ 160 , 161 ]. Fifth, psychiatric medications have been proposed as potential moderators of COVID-19 disease severity [ 143 ], although teasing apart the effects of psychiatric disorders from comorbid medical conditions, and the direct pharmacological effect of various classes of anti-depressants, mood-stabilizers, and anti-psychotic medications, is challenging. Sixth, social and lifestyle factors associated with psychiatric illnesses such as substance use [ 162 , 163 ], lack of exercise [ 164 ], sleep disturbance [ 131 ], and social isolation [ 165 ] have all been independently linked with impaired viral immunity or susceptibility to COVID-19, more specifically.…”
Section: Depression and Other Psychiatric Disorders As Risk Factors F...mentioning
confidence: 99%
“…The COVID-19 crisis has also been shown to have implications for wellbeing as measured by depressive symptoms (Oyenubi et al, 2021;Posel et al, 2021) and self-assessed health . This is important for the prevalence of depressive symptoms across socioeconomic status during the pandemic since individuals with pre-existing mental health issues have been shown to be at higher risk of hospitalization and death due to COVID-19 (Ceban et al, 2021;De Hert et al, 2021).…”
Section: Introductionmentioning
confidence: 99%